Engineered Carbon Electrodes for High Performance Capacitive and Hybrid Energy Storage. (March 2021) - Surendran, Vishnu; Arya, Raveendran S.; Vineesh, Thazhe Veettil; Babu, Binson; Shaijumon, Manikoth M.
Highlights: All-carbon-based capacitive and hybrid storage devices are fabricated. Both electrodes are derived from a single precursor- Coconut sprout. Use of coconut sprout as separator with excellent stability is demonstrated. Hybrid device shows specific energy of 88 Wh kg −1  at a specific power of 273 W kg −1 . The charge storage mechanism at anode is explored through various methods. ABSTRACT: Here we demonstrate, the use of a bio-material coconut sprout (CS) as a single precursor to prepare highly efficient carbon-based electrode materials and a separator with excellent mechanical properties and good chemical stability, for both capacitive and hybrid energy storage systems. A hybrid sodium ion capacitor is fabricated using hard carbon derived from CS (CSDHC) as Na + intercalating anode and high specific surface area porous carbon (SSA ~2000 m 2 g −1 ) derived through KOH activation of CS (CSDPC) as a cathode material. The full cell device delivered specific energy of 88 Wh kg −1  at a specific power of 273 W kg −1, when cycled in a potential window of 1.5 - 4.0 V, and showed remarkable rate capability along with excellent long-term cycling stability. Further, symmetric supercapacitor cells are assembled using CSDPC in both aqueous and organic-based electrolytes, which delivered maximum specific energy of 24.7 Wh kg −1 at a specific power of 7.3 kW kg −1 . Most interestingly, we used the spongy sprout as the separator in all the assembled cells, which showed excellent mechanical properties and good chemical stability even after 10000 cycles of charge and discharge. The present study will pave the way to explore bio-derived engineered carbon materials with unique structure design and tunability for energy-related applications Graphical Abstract: Image, graphical abstract